Heat-related rest-break recommendations for farmworkers in California based on wet-bulb globe temperature - Sagar P. Parajuli; Trent Biggs; Nicolas Lopez Galvez; Penelope Quintana; Haley Ciborowski; Fernando De Sales; Miguel Angel Zavala Perez; Charles Jones; Callum Thompson; Stephanie Hurtado-Gonzalez; Samantha Madonia; Samuel S. P. Shen (Communications Earth & Environment)
Abstract Extreme heat is a global public health concern that is becoming more frequent and severe in recent periods. Translating Earth science data into policy-relevant metrics, such as rest breaks, is challenging but needed to protect outdoor workers from heat stress. Here, we determine rest-break requirements for the farmworkers of the Imperial and Coachella Valleys in southern California, which have a high poverty rate and the highest heat-illness rates in California. We used high-resolution outputs from a validated Weather Research and Forecasting Model (WRF) at 1-km grid resolution that includes irrigation, a key modulator of heat stress in the study region. We calculated exceedances of heat stress indicators under three existing policy guidelines that use wet-bulb globe temperature (WBGT), heat index (HI), or dry-bulb temperature (DBT), and translated them into rest breaks needed for farmworker safety. WBGT-based rest minutes are most sensitive to the spatiotemporal variation in heat exposure compared to DBT or HI and vary with acclimatization status, season, and work shifts. Recommended rest breaks to protect farmworkers from heat stress range from 2 to 32 min per work-hour between April and August. Although results are specific to California, our method is adaptable for calculating region-specific rest break requirements worldwide.